Consumer Preference for Mid-Cost Housing Based on Their Social Stratification in Special Region of Yogyakarta - Hidayati, Wahyu; Bagaskara, Bagaskara (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2024)
In Special Region of Yogyakarta, housing backlog is caused by supply and demand gap for mid-cost housing, limited capacity of developers, and low housing affordability for low-income people. This research aims to analyze the influence of social stratification on consumer preference for mid cost housing on housing developments and on non-clustered housing areas as well as the desired attributes of mid-cost housing. This research employed descriptive and inductive statistics with chi square test. Purposive sampling was employed with a sample size of 220 respondents were collected through interviews, questionnaires, observations, and literature review. The result show social stratification influences consumer preference for mid-cost housing on both areas. The desired attributes included location, physical characteristics, legal documents, neighborhood, and amenities. It is important for the local government to implement relevant policies and mortgage financing policies as well as provide supporting infrastructure and facilities for its development to ensure residential areas contribute to regional development.